Determinantes genéticos, bioquímicos e clínicos na resposta ao uso de hidroxiureia na doença falciforme - Belini Júnior, Édis [UNESP] (2014)
Sickle cell disease (SCD) is characterized by a very heterogeneous clinical ranging from patients who have normal life expectancy with relatively few complications; others can have severe complications such as pulmonary hypertension, priapism, stroke, leg ulceration, recurrent painful episodes, acute chest syndrome (ACS) and avascular necrosis of bone (AVN). Treatment with hydroxyurea (HU) has become more adopted by medical and HU experience in DF has been accumulated over the last 25 years. However, many studies have been designed to investigate the genetic variations that may explain why some patients tolerate and respond to the use of HU, while others still need to be treated with alternative therapies. In view of this, we aimed to evaluate the response to HU treatment considering the genetic polymorphisms influence involved in the pathophysiology of SCD. For this, we used the calculator severity of DF (CGDF); detected the polymorphisms -509C/T (TGFB1), -308G/A (TNFA), 313 A/G (GSTP1), -786T/C (NOS3), null (GSTM1 and GSTT1), we assessed markers of oxidative stress (catalase, glutathione peroxidase-GPx, glutathione S-transferase-GST, glutathione reductase-GR and the thiobarbituric acid reactive species-TBARS). The study involved 520 patients older than 5 years, from the Instituto de Hematologia do Rio de Janeiro/RJ-HEMORIO. The CGDF was validated for Brazilian patients and severity scores were related to oxidative stress markers. The presence of the GSTM1 null allele increased the occurrence chance of priapism in SCD patients. TGFB1 gene mutation had a protective effect on the occurrence of STA and leg ulcers, and the presence of the mutant allele for the NOS3 gene decreased the occurrence chance of retinopathy and priapism. For biochemical markers, we found that the decreased of enzymes activity (catalase, Gpx and GR), and the increased in GST activity were associated with greater SCD severity. In addition, lipid peroxidation levels ...